A review: use of whole-body vibration on human performance and recovery - Jeronimo, L.; Pelot, T. (Olympic & Paralympic Coach, 2016)
In recent years, the use of whole body vibration (WBV) has gained popularity as a potential training modality for enhancing recovery and athletic performance. Recent documentation has shown improvement in strength and power with vibratory stimulation (Issurin, 1999; Delecluse, 2003; Rønnestad, 2009; Rønnestad, 2009; Stewart, 2009). WBV involves a subject standing or performing exercises on a platform generating vertical and horizontal vibrations at various frequencies (Delecluse, 2003). Additionally, studies have shown a decrease in delayed-onset muscle soreness (DOMS) with the implementation of WBV (Aminian-Far,2011; Bakhtiary, 2007; Rhea, 2009). Since exercise induced muscle damage (EIMD) may jeopardize training status for athletes, recovering quickly will enable athletes to train more frequently, thus increasing performance. This review will attempt to provide a coherent interpretation of existing research to help explain potential benefits behind WBV training.